Science Communication Demands a Critical Approach That Centers Inclusion, Equity, and Intersectionality - Canfield, Katherine N.; Menezes, Sunshine; Matsuda, Shayle B.; Moore, Amelia; Mosley Austin, Alycia N.; Dewsbury, Bryan M.; Feliú-Mójer, Mónica I.; McDuffie, Katharine W. B.; Moore, Kendall; Reich, Christine A.; Smith, Hollie M.; Taylor, Cynthia (Frontiers in Communication, 2020)
We live in an era of abundant scientific information, yet access to information and to opportunities for substantive public engagement with the processes and outcomes of science are still inequitably distributed. Even with increasing interest in science communication and public engagement with science, historically marginalized and minoritized individuals and communities are largely overlooked and undervalued in these efforts. To address this gap, this paper aims to define inclusive science communication and clarify and amplify the field. We present inclusive science communication as one path forward to redress the systemic problems of inequitable access to and engagement with STEMM (science, technology, engineering, mathematics, and medicine). We describe the first national Inclusive Science Communication (InclusiveSciComm) Symposium held in the U.S. Based on the experience of organizing the symposium, we discuss recommendations for other convenings to help build a community of practice for inclusive science communication. In both research and practice, we advocate for more experimentation to help make inclusive science communication the future of science communication writ large, in order to engage diverse publics in their multiple ways of knowing and expand a sense of belonging in STEMM.